Effects of water–nitrogen coupling on water and salt environment and root distribution in Suaeda salsa - Xu, Qiang; Liu, Hongguang; Li, Mingsi; Ping, Gong; Li, Pengfei; Xu, Yibin; Zhang, Qian; Xia, Hanji (Frontiers in Plant Science, 2024)
Understanding the spatial distribution of crop roots is crucial for effectively managing crop water and fertilizer. We investigate the effects of water–nitrogen coupling on the water–salt environment and root distribution in the root zone of S. salsa. Three irrigation levels were established, calculated according to 0.35 (W1), 0.50 (W2), and 0.65 (W3) of local ET0. The three nitrogen levels were 150 (N1), 250 (N2), and 350 (N3) kg·hm−2 in a complete combination design. With the augmentation of irrigation water and nitrogen application, the total root weight density of the root system of Suaeda salsa increased from 17.18×10-3 g·cm-3 to 27.91×10-3 g·cm-3. The distribution of soil water suction significantly influences the root distribution of Suaeda salsa in saline soil, causing a transition from a narrow deep type to a wide shallow type. Under the W2 irrigation level, soil water suction ranges from 1485.60 to 1726.59 KPa, which can provide water for S. salsa.it becomes feasible to attain the necessary water and salt environment for the growth and development of S. salsa, resulting in the attainment of maximum biomass, ash content, and salt uptake. No significant differences in the biomass, ash content, and salt uptake of S. salsa was noted between N2 and N3 nitrogen application levels (p > 0.05).The optimal irrigation volume and nitrogen application level were 0.50 ET0 and 250 kg·hm−2, respectively. The results of this study provide a scientific basis for the large-scale planting of S. salsa in extreme arid areas to improve and utilize saline wastelands.